Multifocal recurrence of medulloblastoma: a long follow-up case study (Medical Journal of Indonesia, 2020)
Medulloblastoma is the most common malignant brain tumor in pediatric patients. Leptomeningeal dissemination often occurs in the spinal canal and rarely into the supratentorial as an extra-axial lesion. This study followed an 8-year progression of multifocal medulloblastoma recurrence as supratentorial metastasis that mimics an intra-axial mass of the temporal lobe. Pathologic examination of the temporal mass showed densely packed small round blue cells that are distributed in a ribboning pattern with areas of necrosis, rosette formation, and mitosis. Ki-67 immunohistochemical staining of the tumor showed a high proliferation index of 40% and revealed positive results for synaptophysin and negative results for glial fibrillary acidic protein and β-catenin. A long follow-up is essential to diagnose the recurrence and elucidate the progression of medulloblastoma.